Modeling the performance of bulk-carriers for Islamic equity investors - Abdullah, Adam; Hassan, Rusni; Kassim, Salina (Islamic Bank Training and Research Academy (IBTRA), 2017)
This paper investigates the performance of bulk-carriers as a primary shipping segment for Islamic equity investors. Shipping is a strong growth industry with 84% of global trade carried by the shipping industry, although 75% of ship lending is debt-based. Moreover, many Islamic investors have minimal exposure to ship-finance and investment. We adopt an investment analysis of a full population of historical data over 20 years, to evaluate performance involving a maritime return on investment, IRR, net yield and standard deviation measures of risk and return. Our findings reveal that whilst earnings are volatile in comparison to capital market expectations, unlevered, tax-free returns on bulk-carrier investments out-perform other assets. By communicating risk and reward more effectively, Islamic equity investors, will realize the benefit of equity finance on the basis of profit sharing, is more efficient at allocating investible resources than debt finance at interest, thereby increasing investment and economic growth.